Consumers' preferences toward attributes of manufactured halal food products - Mohayidin, Mohd Ghazali; Kamarulzaman, Nitty Hirawaty (Routledge, 2014)
Consumers' buying decisions are invariably influenced by their religion and culture. In Islam, the foods they consume must be halal or permissible according to the Islamic principles. However, there are other food attributes such as brand, price, promotion, and safety assurance that may also influence consumers' decisions. This article aims to evaluate consumers' preferences toward various attributes of the manufactured halal food sold in supermarkets. The focus is on halal certification because consumers, especially Muslims, need the assurance that the food they purchased is really halal. Two hundred eighty-eight people agreed to participate by providing their perceptions and preferences toward food product attributes. Certified halal food product gained the highest utility score and was the most important attribute.